The Impact of Digital Payment on Banking Stability - Muthia Hanan Bachri; Irwan Adi Ekaputra (Eduvest - Journal of Universal Studies, 2024)
Previous studies provides conclusions regarding the relationship between digital payments and banking stability in a particular country. Therefore, this research wants to see how the growth of digital payments impacts banking stability in 110 countries in the world from 2017 – 2022. This study explores the relationship between digital payments and banking stability using a panel data regression model. Digital payment transactions are proxied by the payment penetration ratio (PPR) while banking stability is proxied by the country's Z-score. This research found a negative correlation between digital payment transactions and banking stability in data from 110 countries. This is possible because of the risks arising from digital payment transactions. Overall, these findings support policies to increase secure payment transactions for banking stability.